PENCIPTAAN KARYA SENI PAKELIRAN SULUH MALAT " KELANA CARANG NAGA PUSPA" - I Gusti Ngurah, Krisna Mahendra; Gumana Putra, I Gusti Ngurah; Sudiana, I Ketut (JURNAL DAMAR PEDALANGAN, 2025)
Emerging from the application and development of traditional wayang performances, a new concept called Pakeliran Suluh Malat was born. The creator implemented elements of traditional performances with a fresh perspective, such as Tembang (Melodies), Antawacana (Rhetoric), Tutur (Adages), and the dramatic structure of the narrative, which became essential elements in Pakeliran Suluh Malat. This performance highlights social issues such as land conversion and government policies, reflecting concerns about the future of the coming generations. The Pakeliran Suluh Malat performance is expected to provide reflection, wisdom, and messages that can be applied in human life. The method used to formulate Pakeliran Suluh Malat is based on Alma M. Hawkins’ approach, adapted by Y. Sumandio Hadi. This method consists of three main stages: exploration, improvisation, and formation. In addition to conveying moral messages, Pakeliran Suluh Malat is rich in aesthetic values. The visual composition presents choreography along with symbols that convey messages through movement, sound, sign language, and verbal language. Thus, Pakeliran Suluh Malat emerges as a new form of performance while maintaining the breath of tradition.